Production of Coconut Milk Cheese and Its Organoleptic Characteristics - Halim, Judella Kusuma; Wangrimen, Gervasius Harwin; Fitriani, Aprilia (Universitas Ahmad Dahlan, 2022)
Cheese is a dairy product that contains lactose so it cannot be consumed by lactose intolerant. Coconut milk can be used as an alternative to produce lactose-free cheese. This study contribution to investigate the effect of coconut milk and soy milk composition on the physical and chemical properties of coconut milk cheese, as well as product acceptability. Direct acidification using lemon juice is used to produce cheese with different coconut milk and soy milk composition (80:20; 70:30; 60:40). The properties assayed were yield, spreadability, and organoleptic. Yield of coconut milk cheese at composition 80:20; 70:30; 60:40 was 37.96%; 34.44%; 31.48%. Spreadability of coconut milk cheese at composition 80:20; 70:30; 60:40 was 9.83 cm; 9.65 cm; 9.53 cm. The difference of coconut milk and soy milk composition affects the physical and organoleptic properties of coconut milk cheese. Decrease in the level of coconut milk substitution and increase in the level of soy milk substitution led to decrease yield and cheese spreadability. Organoleptic score below 3 indicates that coconut milk cheese acceptability was still low.